Electrochemical synthesis and characterization of self-doped aniline 2-sulfonic acid-modified flexible electrode with high areal capacitance and rate capability for supercapacitors - Yazar, Sibel; Sahin, Yucel; Arvas, Melih Besir (ELSEVIER SCIENCE SA, 2022)
Polypyrrole and aniline 2-sulfonic acid (CFt/PPy/ASA(0.03) composite was synthesized on carbon felt (CFt) under acid conditions. Here, we report investigated in concentration of ASA on the electropolymerization of the PPy, to improve performance of supercapacitor by a facile and effective one-step electropolymerization method. To form a 3D carbon felt, homogeneous and large grains are grown on the surface with the addition of ASA, which provides high active mass and potential redox materials of pseudocapacitive supercapacitor. The flexible electrode shows a high specific areal capacitance 4000 mF.cm(-2) at the scan rate of 10 mV.s(-1) and excellent rate capability. A symmetric supercapacitor was also assembled with 1 M H2SO4 electrolyte which delivers a maximum energy density of 18.8 Wh.kg(-1) at a power density of 312.5 kW.kg(-1), and a maximum power density of 1875 kWh.kg(-1) can be reached up while delivering a energy density 2.2 Wh.kg(-1). The device displays retention of capacitance performance 82.7% even after 2500 cycles in aqueous electrolyte on the PPy-based materials. Therefore, (CFt/PPy/ASA(0.03) electrode has an important role in practical applications of flexible, wearable and portable electronics.
Keywords: Supercapacitor; Conducting polymer; Aqueous electrolyte; Electropolymerization; Rate-capability; ALL-SOLID-STATE; HIGH-PERFORMANCE; POLYPYRROLE FILMS; CARBON MATERIALS; GRAPHENE OXIDE; ENERGY DENSITY; COMPOSITE; NANOTUBES; POLYMERS; Materials Science; Physics; Polymer Science